2017
DOI: 10.1186/s12891-017-1577-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover and periprosthetic bone loss after cementless total hip arthroplasty can be restored by zoledronic acid: a prospective, randomized, open-label, controlled trial

Abstract: BackgroundAlthough the loss of bone mineral density (BMD) after total hip arthroplasty (THA) is a known problem, it remains unresolved. This study prospectively examined the effect of zoledronic acid (ZA) on bone turnover and BMD after cementless THA.MethodsBetween January 2010 and August 2011, 60 patients who underwent cementless THA were randomly assigned to receive either ZA infusion or placebo (0.9% normal saline only) postoperatively. ZA was administered at 2 day and 1 year postoperatively. Periprosthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
(51 reference statements)
2
19
0
Order By: Relevance
“…However, subsequently, the 5-year BMD changes were not significantly different between groups. Huang et al (2017) 28 showed that zoledronic acid (ZA), a third-generation bisphosphonate, could effectively revert the loss of periprosthetic BMD, especially in the proximal femur (zones 1 and 7), which is similar to the present results. All these studies mentioned above did not evaluate patients' QoL after THA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, subsequently, the 5-year BMD changes were not significantly different between groups. Huang et al (2017) 28 showed that zoledronic acid (ZA), a third-generation bisphosphonate, could effectively revert the loss of periprosthetic BMD, especially in the proximal femur (zones 1 and 7), which is similar to the present results. All these studies mentioned above did not evaluate patients' QoL after THA.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have evaluated the effects of other antiosteoporosis drugs on the prevention of periprosthetic bone loss around the femoral stem, and some have found positive results [25][26][27][28] . Muren et al 25 reported that the effect of risedronate on preventing periprosthetic bone loss postoperatively failed to be seen at 4 years with a cohort of 61 patients.…”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5)(6)(7)(8)(9) A number of studies have investigated the efficacy of bisphosphonates for the preservation of periprosthetic BMD after THA, which found that periprosthetic bone loss could be effectively arrested or even reverted. (9)(10)(11) The current limited data demonstrated that denosumab is at least as effective as bisphosphonates in decreasing bone resorption, and denosumab even increases bone mass in some Gruen zones, although the exact BMD changes in each Gruen zone were not given in detail in the present study. (1,2) However, both studies found that the periprosthetic BMDs of the denosumab group approached the levels of the placebo group after discontinuation of denosumab, although the rebound effect was only observed in the present study and might have been missed in the other study.…”
Section: College Beijing Chinamentioning
confidence: 53%
“…As we mentioned before, not all the patients experienced periprosthetic bone loss after THA [7,8], while early medical intervention was recommended for all the patients underwent THA [5,6]. Numerous studies demonstrated that the administration of bisphosphonate effectively inhibited postoperative periprosthetic bone loss from one to three years after the THA [13,[26][27][28][29]. However, there is no clear guideline regarding the indication of bisphosphonate treatment for patients underwent THA, especially for those without osteoporosis and osteopenia.…”
Section: Discussionmentioning
confidence: 99%